The efficacy and safety of Chinese herbal medicine in the treatment of painful diabetic neuropathy: A systematic review and meta-analysis - Song, Min; Huai, Baogeng; Shi, Zhenpeng; Li, Wenyi; Xi, Yutan; Liu, Zhenguo; Zhang, Jihang; Zhou, Junyu; Qiao, Yun; Liu, Deshan (Frontiers in Pharmacology, 2023)
Abstract： Objective: The objective of this systematic review and meta-analysis is to assess the effectiveness and security of Chinese herbal medicine (CHM) in the therapy of painful diabetic neuropathy (PDN). Methods: We searched databases for randomized controlled trials (RCTs) of CHM in the treatment of PDN. Outcome indicators included nerve conduction velocity, clinical efficiency, pain score, TCM syndrome score, and adverse events. Stata 16.0 was used to carry out the Meta-analysis. Results: A total of 21 RCTs with 1,737 participants were included. This meta-analysis found that using CHM as adjuvant treatment or as monotherapy for PDN can improve SCV of median nerve [mean difference(MD) = 3.56, 95 % Confidence interval (CI) ( 2.19, 4.92 ) ], MCV of median nerve [ MD = 3.82, 95 % CI ( 2.51, 5.12 ) ], SCV of common peroneal nerve [ MD = 4.16, 95 % CI ( 1.62, 6.70 ) ], MCV of common peroneal nerve [ MD = 4.37, 95 % CI ( 1.82, 6.93 ) ], SCV of gastrocnemius nerve [ MD = 4.95, 95 % CI ( 3.52, 6.37 ) ], SCV of tibial nerve [ MD = 3.17, 95 % CI ( − 2.64, 8.99 ) ], MCV of tibial nerve [MD=6.30,95%CI（5.00，7.60）] and clinical effective rate [ odds ratio (OR) = 4.00, 95 % CI ( 2.89, 5.52 ) ] and reduce pain score [standardized mean difference (SMD)= -2.23,95 % CI ( -3.04, -1.41 ) ], TCM syndrome score [ MD = -4.70,95 % CI ( -6.61, -2.80 ) ]. In addition, compared to the control group, adverse events of Chinese medicine intervention occurred less. Conclusion: CHM as adjuvant therapy or single treatment has a good curative effect and is safe for patients with PDN, which is worthy of clinical promotion and use, however; higher quality clinical studies are still needed to prove.